2010
DOI: 10.1590/s0103-49792010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Contratos de boca: a institucionalização da precariedade na construção civil

Abstract: Este artigo analisa a percepção de operários da construção de edificações sobre o contexto de vulnerabilidade social, marcado pela precarização crescente dos contratos de trabalho. Foram entrevistados vinte trabalhadores da cidade de São Carlos (Brasil), recuperando suas trajetórias de trabalho. Por meio da análise qualitativa das entrevistas, foi possível verificar a vulnerabilidade e as formas variadas de contratos de trabalho e de remuneração. Apesar da precariedade das relações de trabalho, metade dos trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Although the scores for physical effort and dehumanization (TD1) were significantly lower, as opposed to what was predicted, we observed that when we constructed the descriptive attributes hierarchy, TD1 moved from the fourth level of the hierarchy in 2011, to level one in 2015, along with recognition and fair treatment. We understood that those results match our prediction for a conformist tendency on the workers' part when perceiving work on a daily basis (Barros & Mendes, 2003;Cockell & Perticarrari, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although the scores for physical effort and dehumanization (TD1) were significantly lower, as opposed to what was predicted, we observed that when we constructed the descriptive attributes hierarchy, TD1 moved from the fourth level of the hierarchy in 2011, to level one in 2015, along with recognition and fair treatment. We understood that those results match our prediction for a conformist tendency on the workers' part when perceiving work on a daily basis (Barros & Mendes, 2003;Cockell & Perticarrari, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…As discussed previously, in the workers' case, these conditions are closely associated with fending for both themselves and their families (Cockell, 2008;Silva & Borges, 2015). The lack of these conditions, which is exacerbated by the economic crisis, affects basic needs directly, since the workers find themselves within the bounds of social exclusion (Cockell & Perticarrari, 2010;Santos, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations